Decision-making in crisis resolution and home treatment teams: The AWARE framework. (19th November 2018) - Lombardo, Chiara; Santos, Mónica; Van Bortel, Tine; Croos, Robert; Arensman, Ella; Kar Ray, Manaan
Abstract : Aims and method: The aim of the study is to improve patient safety by identifying factors influencing gatekeeping decisions by crisis resolution and home treatment teams. A theoretical sampling method was used to recruit clinicians. Semi-structured interviews to elicit various aspects of clinical decision-making were carried out. The transcripts were thematically analysed using a grounded theory approach. Results: Patient needs (safety and treatment) was the primary driver behind decisions. The research also revealed that information gathered was processed using heuristics. We identified five key themes (anxiety, weighting, agenda, resource and experience), which were constructed into an acronym 'AWARE'. Clinical implications: AWARE provides a framework to make explicit drivers for decision-making that are often implicit. Incorporating these drivers into reflective practice will help staff be more mindful of undue influences and result in improved clinical decisions. Declaration of interest: None.